Characteristics of cirrus clouds over ALOMAR and their dependence on atmospheric conditions - Larsgård, Nina Elisabeth (2008)
This thesis is a short investigation of cirrus clouds above the ALOMAR observatory at Andøya. Ice clouds are one of the main uncertainties in the cloud effects in atmospheric modelling. Especially ice clouds in the arctic need further investigation. This study uses the Tropospheric Lidar at ALOMAR to investigate some aspects, as cloud top and base heights, optical depth and ice crystal shape, of ice clouds above Andøya(69°N 16°E). The LIDAR is an instrument well suited to investigate the smaller particles in the atmosphere as it operates on shorter wavelengths than for example the RADAR. A short one year climatology has been given as an overview of the cloud occurrence in the LIDAR data from 2006. The cloud altitudes have also been found from the LIDAR data using existing algorithms, and along with temperature data from radiosondes have these altitudes been compared with cloud data from the CALIPSO satellite. The CALIPSO satellite carries a LIDAR system (CALIOP) that makes vertical profiles of the atmosphere. The height is found by comparing the LIDAR signal to a threshold found in a cloud and aerosol free region above the cloud. The optical depth has been extracted from the LIDAR signal with the particular integration method from Cadet et al. (2005) The ratio between the two polarizations of the 532 nm channel has been found to investigate the shape of the ice crystals. The connection between the weather situation in each case and the clouds found in the LIDAR data is also shown in this thesis. The height results show that the clouds found in the ALOMAR data is mostly cirrus clouds because of their high altitude and low temperatures. The optical depth classified the clouds investigated as thin to opaque in two of the cases, and the last case was classified as an opaque cirrus to thin altostratus. The depolarization ratio results show that at least for the cases used in this thesis will often some parts of the cirrus clouds consist of horizontally oriented ice crystals. They also seem to consist mostly of ...